Analisis Komposisi dan Efisiensi Biaya Kontruksi Berdasarkan Rencana Anggaran Biaya (RAB) pada Proyek Rehabilitasi Kantor Kecamatan Wajak Kabupaten Malang - Aura Aldamah Dea Putri; Tri Kuncoro; Lakshita Umanis Fauzi; Haura Inas Fibrilian (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the composition and cost efficiency of the construction project for the rehabilitation of the Wajak Subdistrict Office in Malang Regency. Cost management is a critical aspect of construction management as it relates to the effective and efficient use of resources. The data used in this study consists of secondary data from the Cost Estimate (RAB) and Unit Price Analysis (AHSP) documents for the 2022 project, which were reanalyzed in 2024. The research method employed is quantitative descriptive analysis using a percentage-based approach to determine the distribution of construction costs by type of work. The results of the study indicate that the total construction cost amounts to Rp199,826,534 with an uneven cost distribution. Retaining wall work constitutes the largest cost component with a contribution of 58.21%, followed by ceiling and roof work at 22.99%, while other works have relatively small contributions. The analysis results indicate that the dominance of costs in formwork work is influenced by the large volume of work and the high material requirements. Therefore, construction cost control needs to be focused on the work with the largest contribution so that cost efficiency can be optimally achieved.